Design of Arduino-Based Dual Axis Solar Tracking System - Yasir Hashim Naif (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
Green and clean energy depends meanly on the Solar energy, especially at urban area. This paper presents the Arduino-based new design of dual-axis solar tracking system with high-efficiency using through the use of five-point sunlight sensors. The main objective of this research is to convert the maximum sunlight to electrical power by auto movement of the solar panel. This research is divided into two stages, first stage related to hardware design and the second related to software development. In hardware design, five light dependent resistors (LDR) have been used for tracking light direction source. Two linear actuators have been used to move the solar panel towards the maximum light intensity direction by using LDR sensors. Moreover, the software is constructed using C++ programming language and uploaded to the Arduino UNO platform. The efficiency of the designed tracking system has been examined and compared with fixed and single axis solar tracker and results shows that the new system has better efficiency than the fixed or single axis  system.Keywords: Arduino, microcontroller, solar panel, sensors, tracking system.